Efektivitas Pengadilan Hak Asasi Manusia di Indonesia - Mohamad Tapril; Adi Nur Rohman (JURNAL HUKUM PELITA, 2025)
This article analyzes the effectiveness of Human Rights (HAM) Courts in Indonesia within the framework of national and international law. Based on Law No. 26 of 2000 on Human Rights Courts, this special court was established to enforce accountability and justice for victims of gross human rights violations and to uphold the principle of non-impunity. However, more than two decades after its establishment, the court’s effectiveness remains questionable, as only a few cases have been prosecuted and most defendants were eventually acquitted. By examining cases such as East Timor (1999), Tanjung Priok (1984), and the Trisakti and Semanggi Tragedies (1998–1999), this study identifies key obstacles stemming from legal, political, and institutional factors. Legally, weaknesses in Law No. 26 of 2000—particularly its limited temporal jurisdiction and the ineffective application of command responsibility—restrict the scope of enforcement. Politically, weak government commitment and interference from power structures undermine judicial independence. Institutionally, poor coordination between the National Commission on Human Rights (Komnas HAM) and the Attorney General’s Office, limited human resources, and inadequate protection for witnesses and victims further reduce the court’s capacity to function effectively. The findings indicate that Indonesia’s Human Rights Courts remain symbolic rather than substantive, failing to deliver justice, truth, and redress for victims. The article argues that reform of the human rights judicial system must involve legal amendments, stronger political will, institutional capacity-building, and the integration of transitional justice principles—namely truth, justice, reparation, and non-recurrence. Through such measures, Human Rights Courts could serve as genuine instruments for upholding the rule of law and human dignity in Indonesia